Prevalence of Delta-Like Protein 3 in a Consecutive Series of Surgically Resected Lung Neuroendocrine Neoplasms - Alì, Greta; Di Stefano, Iosè; Poma, Anello Marcello; Ricci, Stefano; Proietti, Agnese; Davini, Federico; Lucchi, Marco; Melfi, Franca; Fontanini, Gabriella (Frontiers in Oncology, 2021)
Delta-like protein 3 (DLL3) is a protein of the Notch pathway, and it is a potential therapeutic target for high-grade lung neuroendocrine tumors (NETs), i.e., small cell lung carcinoma (SCLC) and large cell neuroendocrine carcinoma (LCNEC). However, DLL3 prevalence in lung NETs and its association with clinicopathological characteristics and prognosis remained unclear. We analyzed the immunohistochemical expression of DLL3 and its prognostic role in a consecutive series of 155 surgically resected lung NETs, including typical carcinoid (TC), atypical carcinoid (AC), LCNEC, and SCLC patients. The DLL3 expression was categorized as high (>50% positive tumor cells) or low (<50%). In addition, tumors were categorized by H-score (i.e., percentage of positive cells by staining intensity, ≥150 vs. <150). DLL3 staining was positive in 99/155 (64%) samples, and high DLL3 expression was frequently observed in high-grade tumors. In detail, 46.9% and 75% of SCLC and 48.8% and 53.7% of LCNEC specimens showed a high DLL3 expression by using H-score and percentage of positive tumor cells, respectively. Regarding low-grade NETs, only 4.9% and 12.2% TCs and 19.5% and 24.4% ACs had high DLL3 expression considering H-score and percentage of positive tumor cells, respectively. High DLL3 expression was associated with advanced American Joint Committee on Cancer (AJCC) stage, peripheral location, and chromogranin A expression in high-grade tumors (p < 0.05). In low-grade NETs, high DLL3 expression was associated with female sex, peripheral location, a higher number of mitoses, higher Ki-67 index, presence of necrosis, and pleural infiltration (p < 0.05). No association was observed between high DLL3 expression and overall survival (OS) and disease-free survival (DFS) in high-grade NETs, whereas high DLL3 expression was associated with lower DFS in ACs (p = 0.01). In conclusion, our study demonstrated a high prevalence of DLL3 expression in high-grade lung NET patients and its association with aggressive clinicopathological features. These findings confirm that DLL3 could represent a useful biomarker for target therapy in high-grade tumors. Our results also suggest that the DLL3 expression could identify a subset of AC tumors with more aggressive behavior, thus providing the basis for new therapeutic options in this group of patients.